2017
DOI: 10.1038/cddis.2017.505
|View full text |Cite
|
Sign up to set email alerts
|

RANKL-mediated harmonious dialogue between fetus and mother guarantees smooth gestation by inducing decidual M2 macrophage polarization

Abstract: Decidual macrophages (dMφ) contribute to maternal–fetal tolerance. However, the mechanism of dMφ differentiation during pregnancy is still largely unknown. Here, we report that receptor activator for nuclear factor-κ B ligand (RANKL), secreted by human embryonic trophoblasts and maternal decidual stromal cells (DSCs), polarizes dMφ toward a M2 phenotype. This polarization is mediated through activation of Akt/signal transducer and activator of transcription 6 (STAT6) signaling, which is associated with the upr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 53 publications
4
50
0
Order By: Relevance
“…The immune cells at the maternal-fetal interface mainly include NK cells, macrophages (Mφ), regulatory T cells and DCs (92). Uterine NK cells and Mφ are the most prominent decidual immune cells; decidual NK cells account for ∼50-70% and decidual macrophages (DM) for 20-25% of all decidual immune cells (103,104). Decidual NK cells have low cytotoxicity as compared to peripheral blood NK cells (105).…”
Section: The Possible Role Of Lactic Acid At the Maternal-fetal Intermentioning
confidence: 99%
“…The immune cells at the maternal-fetal interface mainly include NK cells, macrophages (Mφ), regulatory T cells and DCs (92). Uterine NK cells and Mφ are the most prominent decidual immune cells; decidual NK cells account for ∼50-70% and decidual macrophages (DM) for 20-25% of all decidual immune cells (103,104). Decidual NK cells have low cytotoxicity as compared to peripheral blood NK cells (105).…”
Section: The Possible Role Of Lactic Acid At the Maternal-fetal Intermentioning
confidence: 99%
“…38 DICs were used for dNK cell isolation using Human NK Cell Isolation Kit (Miltenyi Biotec) following the manufacturer's protocol. Using this method, 98% of cells obtained were vimentin + cytokeratin (CK)7 − DSCs and CD45 + DICs as previously reported.…”
Section: Cell Isolation and Culturementioning
confidence: 99%
“…Using this method, 98% of cells obtained were vimentin + cytokeratin (CK)7 − DSCs and CD45 + DICs as previously reported. 38 DICs were used for dNK cell isolation using Human NK Cell Isolation Kit (Miltenyi Biotec) following the manufacturer's protocol.…”
Section: Cell Isolation and Culturementioning
confidence: 99%
“…23 In addition to important roles in immune surveillance, dNK participates in two processes necessary for implantation of the blastocyst and development of the placenta: (a) participation in the process of invasion of the trophoblast and (b) a role in angiogenesis. [24][25][26] Decidual NK may differentiate locally under the influence of tissue-derived TGF-β produced by DSCs. [24][25][26] Decidual NK may differentiate locally under the influence of tissue-derived TGF-β produced by DSCs.…”
Section: Discussionmentioning
confidence: 99%
“…7 Numerous studies have demonstrated that DSCs act as key gatekeepers and chief modulators of immune cells at the maternal-fetal interface. [24][25][26] Decidual NK may differentiate locally under the influence of tissue-derived TGF-β produced by DSCs. 21 Progesterone, human chorionic gonadotropin, and prolactin may have an indirect role in priming DSCs or directly acting on NK cells.…”
Section: Discussionmentioning
confidence: 99%